1963
DOI: 10.1063/1.1733806
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Pressure of Liquid Bismuth

Abstract: The vapor pressure of liquid bismuth in the temperature range 800°—1050°K has been measured by the torsion-effusion method. The values obtained are represented by the equation: log10p (mm Hg) = 8.579— (10 108/T). A few separate Knudsen measurements have been performed in the same temperature range and the results used to calculate the molecular weight of bismuth vapor, and thus the heat of dissociation for the reaction ½ Bi2→Bi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1971
1971
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…The thermodynamic analysis of such a situation becomes complicated, especially, in the absence of even the most primitive data that takes cognizance of such a possibility. For example, earlier measurements on the vapor pressure of liquid bismuth by Knudsen torsioneffusion, vacuum microbalance gravimetry and quasistatic methods [13][14][15][16][17] in a wide range of temperatures, have indicated that the vapor phase consists of $55-65 mol.% of Bi 2 species and 35-45 mol.% of Bi monomer. On the other hand, the vapors of lead were found to be monoatomic [17].…”
Section: Methodsmentioning
confidence: 99%
“…The thermodynamic analysis of such a situation becomes complicated, especially, in the absence of even the most primitive data that takes cognizance of such a possibility. For example, earlier measurements on the vapor pressure of liquid bismuth by Knudsen torsioneffusion, vacuum microbalance gravimetry and quasistatic methods [13][14][15][16][17] in a wide range of temperatures, have indicated that the vapor phase consists of $55-65 mol.% of Bi 2 species and 35-45 mol.% of Bi monomer. On the other hand, the vapors of lead were found to be monoatomic [17].…”
Section: Methodsmentioning
confidence: 99%
“…These temperatures should translate to a bismuth vapor pressure on the order of 1 torr (130 Pa) 3,4 . Due to the mixing of cold argon gas with the bismuth vapor (as well as errors due to conduction and radiation from the thermocouple bead), a thermocouple measurement of the gas near the center of the chamber typically reads a maximum temperature near 600ºC.…”
Section: Bismuth Heat Pipe Apparatusmentioning
confidence: 99%
“…Slight adjustments in the positioning of the IR temperature detector result in a change of the measured temperature from tens to hundreds of degrees Celsius because different parts of the inner surface are at vastly different temperatures. It is nearly impossible to pinpoint the site of maximum temperature, and to be sure that that is the temperature controlling the bismuth vapor pressure; in the regime of 800-900ºC, the vapor pressure changes by a factor of 2-3 roughly every 50ºC 3,4 , so errors here can be significant. It is also possible that the vapor pressure of the bismuth is not only influenced by the surface temperature of the mesh, but also by the temperature of the colder argon gas in the chamber.…”
Section: Electrical Character Of Bi Vapormentioning
confidence: 99%
“…The vapor pressure P o of Bi and its temperature dependence has been extensively studied in the past. 27,28 It has been shown that it does not have a simple Arrhenius behavior from 350 to 1000°C. It is nearly negligible below 350°C and increases for higher temperatures, but not monotonically.…”
mentioning
confidence: 99%